To multiply the rational expressions \(\frac{x^2 - 11x + 30}{x^2 - 25} \cdot \frac{x^2 + 8x + 15}{x^2 - 3x - 18}\), we first need to factor each polynomial where possible.
Step 1: Factor the polynomials.
First expression:
-
Factor \(x^2 - 11x + 30\):
- This factors to \((x - 5)(x - 6)\).
-
Factor \(x^2 - 25\) (difference of squares):
- This factors to \((x - 5)(x + 5)\).
Second expression:
-
Factor \(x^2 + 8x + 15\):
- This factors to \((x + 3)(x + 5)\).
-
Factor \(x^2 - 3x - 18\):
- This factors to \((x - 6)(x + 3)\).
Step 2: Rewrite the multiplication with the simplified factors:
Now we can rewrite the original multiplication:
\[ \frac{(x - 5)(x - 6)}{(x - 5)(x + 5)} \cdot \frac{(x + 3)(x + 5)}{(x - 6)(x + 3)} \]
Step 3: Cancel common factors:
Cancel the common factors in the numerator and denominator:
- \( (x - 5) \) in the numerator and denominator.
- \( (x + 3) \) in the numerator and denominator.
- \( (x - 6) \) in the numerator and denominator.
Resulting expression:
After canceling, the simplified expression is:
\[ \frac{1}{x + 5} \]
Step 4: Identify restrictions on the variable:
To find the restrictions, we must identify values of \(x\) that make the original denominators zero.
-
From \(x^2 - 25 = 0\):
- \(x - 5 = 0 \Rightarrow x = 5\)
- \(x + 5 = 0 \Rightarrow x = -5\)
-
From \(x^2 - 3x - 18 = 0\):
- \(x - 6 = 0 \Rightarrow x = 6\)
- \(x + 3 = 0 \Rightarrow x = -3\)
Conclusion:
The variable restrictions are \(x \neq -5, 5, -3, 6\).
Thus, the final answer is: \[ \frac{1}{x + 5} \]
Restrictions on \(x\):
-
- \(x \neq -5, 5, -3, 6\)